2012
DOI: 10.1093/dnares/dss029
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Mapping in Brassica rapa Revealed the Structural and Functional Conservation of Genetic Loci Governing Morphological and Yield Component Traits in the A, B, and C Subgenomes of Brassica Species

Abstract: Brassica rapa is an important crop species that produces vegetables, oilseed, and fodder. Although many studies reported quantitative trait loci (QTL) mapping, the genes governing most of its economically important traits are still unknown. In this study, we report QTL mapping for morphological and yield component traits in B. rapa and comparative map alignment between B. rapa, B. napus, B. juncea, and Arabidopsis thaliana to identify candidate genes and conserved QTL blocks between them. A total of 95 QTL wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…In addition, the two parental species have diverged more recently compared to other polyploid species such as cotton [14, 50]. Li et al [51] recently identified QTL for morphological and yield component traits in duplicated regions within the A genome of B. rapa and in homoeologous regions between the A, B, and C genomes of B. rapa , B. juncea and B. napus , which supports the strong level of conservation between Brassica genomes.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the two parental species have diverged more recently compared to other polyploid species such as cotton [14, 50]. Li et al [51] recently identified QTL for morphological and yield component traits in duplicated regions within the A genome of B. rapa and in homoeologous regions between the A, B, and C genomes of B. rapa , B. juncea and B. napus , which supports the strong level of conservation between Brassica genomes.…”
Section: Discussionmentioning
confidence: 91%
“…Brassica rapa (2n =20, AA) is a diploid crop in this family, which is currently widely cultivated in China, Japan, Korea, India, Canada, and Europe to produce vegetable, oilseed and fodder (Hirai and Matsumoto 2007;Li et al 2013). Since Ogura (1968) first reported the CMS line of radish, a number of F1 hybrid cultivars have been developed using the Ogura CMS system in many economically important Brassica family crops.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze nucleotide polymorphisms in CCA1 associated with variation in flowering, two inbred lines of B. rapa ssp. pekinensis with different flowering phenotypes, Chiifu and Kenshin (Li et al 2013), and an RCBr (IBM-218-DH1) were selecte`d as reference lines. In addition, leaf samples for inbred lines of B. rapa were obtained from three different Korean seed companies: Hankook Seed Co. (indicated by CI or HS in line names), Nonghyup Seed Co. (indicated by BN or NS in line names) and Woori Seed Co.…”
Section: Plant Materialsmentioning
confidence: 99%